RANCANG BANGUN DIGITAL PICKING SYSTEM BERBASIS ARDUINO MEGA 2560 PADA LINE PRODUKSI FINAL ASSEMBLY WIRING HARNESS - Luki Handoko; Moch. Rusli; Bambang Siswojo (Jurnal Mahasiswa TEUB, 2023)
In wiring harness production activities there are 4 production models and 82 production components, some of which have similarities and differences in components. This affects production activities that can trigger errors in the production of goods that are not in accordance with specifications which are generally caused by errors in taking production components. In September 2022 there were 358 wiring harness defective products, of which 132 defective products were caused by errors ininserting the wire into the connector. With this problem, it is necessary to design a method to reduce the yield of defective products. Digital picking system based on Arduino Mega 2560 is designed as a production material management method in the final assembly wiring harness line area. The results of the application of the digital picking system in October obtained 70 units of defective products. Defective products decreased from 358 units in September to 70 units in October. Index Terms—defect product, digital picking system, wiring harness.